A comparative study of the dress, food and leisure of domestic servants in France and Britain, 1900-1939 - Louvier, F (2019)
This thesis is a comparative study of the everyday lives of French and British female domestic servants between 1900 and 1939. Despite making-up nearly half of the female workforce in both countries, the experiences of servants are hard to access. To overcome this problem, the thesis relies on a large sample of French and British servants’ autobiographies. Autobiographies have been used by historians primarily to document the economic struggles these women faced and the social trajectories they followed. However, autobiographies are also bursting with revealing digressions and significant little details about servants’ lives. This thesis seizes upon these insights by actively reading at the margins of servants’ stories. It concentrates on three themes which were most present in servants’ accounts: dress, food and leisure. What servants wore, what they ate and what they did in their free time played a key role in their negotiations of authority and the construction of class, gender, generational and regional identities. The thesis combines this focus on the micro-level of domestic servants’ lives with a comparative analysis which contextualises servants’ testimonies within two different social, cultural and economic environments. It shows how contrasting levels of industrialisation, urbanisation and land ownership as well as divergent forms of family structures and gender norms shaped French and British servants’ world and identities. Ultimately, this comparative study of French and British servants’ experiences with dress, food and leisure leads us to interrogate what it meant to be a servant and deconstruct the category of ‘servanthood’ in the first half of the twentieth century.